Aplikasi Bata Api pada Modifikasi Tungku Pemasakan Keripik Singkong IKM Desa Purworejo Kecamatan Negerikaton, Kabupaten Pesawaran - Wardono, Herry; Hanif, Muhammad; Risano, A. Yudi Eka (Nemui Nyimah, 2021)
The communities of cassava chips apply conventional cooking stoves, which are wasteful of fuel, high air pollution, unclean working environment, and cracks quickly. The technology of refractory brick stove with a modification of the combustion chamber is applied to this cooking stove. A new furnace was made using SK-34 refractory bricks. The stove construction requires little skill and is easy to implement. The results obtained from the stove are much more robust, fuel-efficient, and a clean, healthy and comfortable working environment. In addition, because it is easy to manufacture, people will easily understand and make their refractory brick stove and maintain it. Using a refractory brick stove to produce 40 kg of cassava chips requires a frying time of 2 hours 22 minutes and consumes 89.4 kg of firewood. Meanwhile, using a conventional stove takes a frying time of 3 hours 23 minutes and consumes 117.3 kg of firewood.